(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2014)
Speech goes in the article about world view priorities of poetic work of Vo-lodymyr Каlashnyk, she is analysed stylistic resources, it is accented foremost on voice and tautology repetitions alliteration, assonance, ring, symphloke), stylistic devices and facilities, that serve for underlining of poetic texts, extend the structure of associative-vivid rows, are educed.